Mewujudkan identitas nasional melalui revitalisasi tradisi lokal di era modern: Strategi pelestarian budaya untuk pembentukan karakter bangsa - Wahyudianto, Muhammad Fahmi (Maliki Interdisciplinary Journal, 2025)
Local tradition revitalization becomes an important strategy in strengthening national identity amidst the massive flow of modernization and globalization. This research aims to analyze the relationship between local cultural preservation and the formation of Indonesian national identity as well as formulate effective revitalization strategies. Using a qualitative approach and literature study, this research analyzes challenges and opportunities in reviving local cultural values and their role in shaping nationalism. Data were collected through literature review of books, scientific journals, government policies, and cultural organization reports. The study results show that strengthening national identity through local traditions can be implemented through five main strategies: (1) local culture-based educational policies, (2) involvement of young generation and creative communities, (3) integration of local culture in digital media, (4) government policies supporting culture, and (5) documentation and digitization of traditions. Case studies of Reog Ponorogo and Batik demonstrate successful transformation of sacred traditions into national cultural symbols. This revitalization is not merely preservation, but value transformation to remain relevant in modern society life. This research concludes that collaboration among government, cultural actors, educational institutions, and civil society is essentialto make local traditions inspire the development of civilized and sovereign national character in the modern era